Palestinian-Israeli conflict: Palestinian officials' perspectives on the George W Bush's administration intervention - Mustafa, EID H.; Abdel Salam, El Fatih Abdullahi (Duke University Press, 2016)
Successive US administrations, including that of George W. Bush, have not recognized Palestinian interests and demands. The Bush administration initially showed a lack of serious intent to intervene in the Palestinian-Israeli conflict and had a negative position toward the Palestinians and their interests. However, subsequent Bush administration mediation of the Palestinian-Israeli conflict gained the Palestinians' acceptance. This essay investigates the motivations and reasons behind the Palestinian officials' endorsement of the mediation. The researchers conducted 6 face-to-face interviews and 112 structured interviews with senior Palestinians, including negotiators, security officials, political leaders, parliamentarians, academicians, and experts in the field.